2021
DOI: 10.1111/iwj.13702
|View full text |Cite
|
Sign up to set email alerts
|

Continuous tension reduction technique in facial scar management: A comparison of W‐plasty and straight‐line closure on aesthetic effects in Asian patients

Abstract: W‐plasty is a very popular scar excisional revision technique. The core of the technique is to break up the scar margins into small triangular components, so as to cause light scattering and make the scar less noticeable. However, due to skin tension, facial incision scars tend to spread. Applying W‐plasty alone cannot achieve the ideal repair effect of facial scars. In this study, we proposed a scar revision technique combined W‐plasty with continuous tension‐reduction (CTR) technique to improve the appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…W-plasty has been applied since decades in facial plastic surgery and remains the first-line treatment modality for repairing malformed facial scars. Its ‘broken-line’ or ‘accordion’ appearance allows the scar to break down into smaller triangles, with at least one side parallel to a poorly defined relaxed skin-tension line (RSTL), which causes light scattering and leads to less conspicuous scars 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…W-plasty has been applied since decades in facial plastic surgery and remains the first-line treatment modality for repairing malformed facial scars. Its ‘broken-line’ or ‘accordion’ appearance allows the scar to break down into smaller triangles, with at least one side parallel to a poorly defined relaxed skin-tension line (RSTL), which causes light scattering and leads to less conspicuous scars 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al has found W-plasty to be more effective when combined with continuous tension-reduction, i.e. tension offloading devices such as steri-strips 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies investigated the adhesion of devices to discharge mechanical stress from the surgical incision [23,28,41]. These mechanisms have been shown in animals to be associated with transcriptional downregulation of inflammatory pathways [45] and have obtained benefits in other similar research, helping to heal and improving their aesthetic appearance [46,47].…”
Section: Discussionmentioning
confidence: 99%